A Comparison between Male and Female Students’ Language Learning Strategies Preference - fauzan ansyari; hasni rahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This research focuses on comparing the language learning strategies preference between male and female students at State Senior High School 12 Pekanbaru. The aim of this research is to find out the language learning strategies of male students of the tenth grade at State Senior High School 12 Pekanbaru, to find out the language learning strategies of female students, and to find out whether there is or no a significant difference on language learning strategies preference between male and female students. A total of 90 male and 90 female students were participated in this research. They were taken from 45% of the total population. By using Simple Random Technique, 9 male and 9 female students were randomly taken from each class. The data were collected by using adapted SILL questionnaire version 7.0 translated to Bahasa Indonesia. By using Independent sample t-test formula on SPSS version 17 the collected data were analyzed. The findings show that both male and female students language learning strategies preference were Metacognitive Strategies, and there is no significant difference on the language learning strategies preference between male and female students in learning English at State Senior High School 12 Pekanbaru. Based on the data analysis, the researchers concluded that there is no significant difference on the language learning strategies preference between male and female of the tenth grade students at State Senior High School 12 Pekanbaru in learning English.